Hubungan Konsumsi Minuman Kemasan, Aktivitas Fisik dan Intensitas Penggunaan Gadget dengan Kejadian Obesitas pada Anak di SD Negeri Percobaan Palangka Raya - Zifora; Tri Widodo; Shinta, Herlina Eka; Putra S, Ravenalla Abdurrahman Al-Hakim Sampurna; Ni Nyoman Sri Yuliani (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Based on RISKESDAS 2018, prevalence of obesity in children 5-12 years in Central Kalimantan as 9.27% with percentage of 13.91% in Palangka Raya. Obesity is the accumulation of excessive fat due to imbalances between energy intake and energy expenditure. Some factors that affect obesity are consumption of packaged beverages, physical activity, and intensity of gadget use. Determining the relationship between consumption of packaged beverages, physical activity, and intensity of gadget use with the incidence of obesity in children. This study used quantitative design with a cross-sectional. Sample was 80 students with simple random sampling. Data analysis used univariate and bivariate. The results showed there is no relationship between consumption of packaged beverages and intensity of gadget use with the incidence of obesity in children, but there is relationship between physical activity with obesity in children at SD Negeri Percobaan Palangka Raya.